Investigation of glibenclamide distribution in animal organs by acute intoxication modeling - Кучер, Тетяна Володимирівна; Мерзлікін, Сергій Іванович; Штриголь, Сергій Юрійович (ScienceRise: Pharmaceutical Science, 2016)
Modeling of the effects of chemical compounds toxic influence, including drugs is an important information source for forensic toxicological studies. Cases of fatal poisoning with glibenclamide, mainly at suicidal overdose, are known. Considering that the substance is being actively metabolised, the information about its distribution in organs and tissues after administration to an organism admission at lethal doses can be useful for selecting of biological objects. Aim. This study is aimed to describe the glibenclamide distribution in organs of laboratory animals using the model of acute intoxication. Methods. The model of the glibenclamide acute intoxication was reproduced using albino rats receiving the drug with tween-80 in suspension orally, considering on their body weight and LD50 of toxicant. For the further studies, liver, kidneys, stomach, intestinal content, heart, and blood of the experimental animals were taken after decapitation. Glibenclamide was isolated from the biological objects by acidulated acetonitrile. The extracts obtained from the organs were purified by TLC, and plasma – by solid-phase extraction on Oasis HLB cartridges. TLC and HPLC methods were applied for identification and quantification of glibenclamide. Results. The study revealed that glibenclamide in the extracts obtained from the biological objects was determined in concentrations 2,2–19,8 µg/ml in sample. The highest concentrations of toxicant were found in the extracts obtained from blood and stomach, lower – in the extract from liver and intestinal contents. The given toxicant was found in the extract obtained from heart at concentration of 4,2 µg/ml in sample, that explains its selective toxicity on myocardium. Considering this data, the directed forensic toxicological studies at case of glibenclamide overdose can be carried out by determination of its native substance. Also, it has been proposed to use the heart as an alternative object for chemico-toxicological analysis of toxicants (besides biological objects recommended by TIAFT). Conclusion. Glibenclamide distribution in animal organs and tissues after administration at lethal doses (the model of acute intoxication) has been established. This modeling allowed to determine biological objects, which can be used for forensic toxicological studies in cases of acute overdose with this toxicant, namely: liver, kidneys, stomach and intestinal contents, heart and blood